Selectivity of Face Aftereffects for Expressions and Anti-Expressions - Juricevic, Igor; Webster, Michael (Frontiers in Psychology, 2012)
Adapting to a facial expression can alter the perceived expression of subsequently viewed faces. However, it remains unclear whether this adaptation affects each expression independently or transfers from one expression to another, and whether this transfer impedes or enhances responses to a different expression. To test for these interactions, we probed the basic expressions of anger, fear, happiness, sadness, surprise, and disgust, adapting to one expression and then testing on all six. Each expression was varied in strength by morphing it with a common neutral facial expression. Observers determined the threshold level required to correctly identify each expression, before or after adapting to a face with a neutral or intense expression. The adaptation was strongly selective for the adapting category; responses to the adapting expression were reduced, while other categories showed little consistent evidence of either suppression or facilitation. In a second experiment we instead compared adaptation to each expression and its anti-expression. The latter are defined by the physically complementary facial configuration, yet appear much more ambiguous as expressions. In this case, for most expressions the opposing faces produced aftereffects of opposite sign in the perceived expression. These biases suggest that the adaptation acts in part by shifting the perceived neutral point for the facial configuration. This is consistent with the pattern of renormalization suggested for adaptation to other facial attributes, and thus may reflect a generic level of configural coding. However, for most categories aftereffects were stronger for expressions than anti-expressions, pointing to the possible influence of an additional component of the adaptation at sites that explicitly represent facial expressions. At either level our results are consistent with other recent work in suggesting that the six expressions are defined by dimensions that are largely independently normalize